Advancing Sustainable Transportation: A Feasibility Study on EV Green Charging Station with Fuzzy Control Systems in France and the Philippines - Nachidi, Meriem Labourel (Archīum Ateneo, 2025)
The transition to Electric Vehicles (EVs) represents a sustainable approach to energy consumption and provides a tangible solution to addressing environmental concerns. Many countries are committed to an energy transition process, placing significant emphasis on energy sobriety and efficiency. Their objectives include widespread development of renewable energies while positioning themselves at the forefront of green technologies for renewable and low-carbon hydrogen production. Additionally, investments are being made to facilitate the transition to clean vehicles. This paper introduces a feasibility study focused on developing charging stations (CSs) powered by Renewable Energy Sources (RESs) for EVs, with a specific emphasis on the French and Philippines contexts, aiming to contribute to the ongoing shift towards sustainable transportation. In addition, a fuzzy logic approach, particularly type 2 fuzzy logic, is utilized in this work in order to control the DC bus voltage and optimize power tracking from the RESs. A simulation example is provided to show the applicability of this study purpose.